Bilirubin inhibits bile acid induced apoptosis in rat hepatocytes. Issue 12 (21st November 2003) - Granato, A; Gores, G; Vilei, M T; Tolando, R; Ferraresso, C; Muraca, M
Abstract : Background and aims: Hydrophobic bile acids contribute to hepatocellular injury in cholestasis and rapidly induce apoptosis in vitro; however, unlike Fas agonists, cholestasis does not cause extensive hepatocyte apoptosis. As antioxidants provide protection against bile acid induced liver injury, our premise was that bilirubin, a free radical scavenger with increased plasma levels in the presence of liver disease, could protect hepatocytes against bile acid induced apoptosis. Methods: Freshly isolated rat hepatocytes were incubated for four hours with 100 μmol/l glycochenodeoxycholate (GCDC) alone or with increasing concentrations of unconjugated (UCB) or conjugated (CB) bilirubin. Results: Both UCB and CB inhibited GCDC induced apoptosis in a dose dependent fashion and suppressed the generation of reactive oxygen species by hepatocytes. Conclusions: The antiapoptotic effect of bilirubin associated with its antioxidant properties indicates that hyperbilirubinaemia may have a protective role in liver disease.